Preventing Occupational Diseases and Injuries in Ukraine: The Socio-Economic Perspective - Berezutska, Natalia; Stytsenko, Tetiana; Berezutskyi, Viacheslav (My University, 2020)
The transition of the Ukrainian economy to market conditions is related to the fact that there is frequently a restriction of the funds allocated for labour protection. Therefore, the main task of improving the safety management system in an enterprise in the context of economic reform is to ensure maximum efficiency, given the existing levels of restrictions on management actions. These tasks can be achieved through the optimal allocation of available human and financial management resources, the correct selection of the number and quality of management personnel, making sound, management decisions which are close to optimal. What is of utmost importance is the availability of complete, objective information about the state of the object of management, the state of injury and occupational diseases in the enterprise and developed and scientifically sound methods of its processing and management decisions. This is impossible without the creation of modern information systems in the field of occupational safety.
Keywords: monograph; occupational diseases; injuries; economics